Managing conflict at work the art of communication - Brown, Rick (Chicago : Jack Wilson and Associates, 1994)
This video shows how to turn conflict and other forms of workplace disagreement into opportunities for improvement
Editor, Patty Kniff Leeds
Host : Mary O' Dowd
Keywords: Conflict management; Interpersonal communication